Análisis de factibilidad para la creación de una planta embotelladora de agua en Peltetec parroquia de Pungala en el 2024 - Loja Llivisaca, Pablo Fernando (2025)
This research project evaluatesthe feasibility of establishing a water bottling plant in the community of Peltetec, located in the parish of Pungalá, in the city of Riobamba, province of Chimborazo. To achieve this objective, three key studies were conducted: a market analysis, a technical-administrative study, and a financial assessment. The market analysis identified local demand for bottled water, providing insight into the project's potential consumer base. The technical-administrative study defined the necessary infrastructure and machinery, and included the design of a plant layout. This layout was optimized using a decision tree algorithm from the field of machine learning to improve the distribution of functional areas within the facility. Additionally, the bottling process was simulated using FlexSim software to evaluate the plant’s operational efficiency. Finally, the financial study assessed the project's economic viability through cash flow projections and key financial indicators, specifically Net Present Value (NPV) and Internal Rate of Return (IRR). The results across three scenarios—optimistic, moderate, and conservative—indicated that the project is financially viable under all conditions analyzed.